Mesenchymal Stem Cells and C-type Natriuretic Peptide Signaling: A Proposal for a New Treatment Approach for Skeletal Dysplasias - Serkant Unal, Murat; Cevik Tufan, Ahmet (Current Stem Cell Research & Therapy, 2016)
Endochondral ossification is under the regulation of endocrine, paracrine and otocrine factors including transforming growth factor-β superfamily members, fibroblast growth factors, retinoids, products of hedgehog gene, parathyroid hormone-related peptide, molecules involved in cell adhesion, and extracellular matrix components. Natriuretic peptide receptor-B, and its ligand C-type natriuretic peptide have also been implicated in the regulation of limb bone development. Results of recent studies are promising in terms of systemic elevation of C-type natriuretic peptide level inducing growth. In addition, same strategy also overcomes the dwarf phenotype of achondroplasia, the most frequently seen skeletal dysplasia in human, in a mouse model. Based on this literature and a series of recent experiments discussed here, this perspective underlines the abundant C-type natriuretic peptide expression in trabecular bone derived mesenchymal stem cells of human, chicken, and rat origin, and proposes the potential use of mesenchymal stem cells as a part of growth inducing treatment strategy in osteochondrodisyplasias in the future.
Keywords: skeletal dysplasia